2018
DOI: 10.1111/bjh.15684
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in multiple myeloma – choice of prophylaxis, role of direct oral anticoagulants and special considerations

Abstract: Summary Multiple myeloma is associated with a significant risk of venous thromboembolism (VTE), causing substantial levels of morbidity and mortality. The thrombogenicity of myeloma is multifactorial, with disease‐ and treatment‐related factors playing important roles. Immunomodulatory drugs (IMiDs) and high‐dose dexamethasone, in particular, are known to enhance the thrombotic potential of myeloma. For this reason, assessment of the VTE risk has long been advocated prior to treatment initiation in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 127 publications
1
52
1
1
Order By: Relevance
“…Conversely, the risk is substantially higher with Rd in combination with proteasome inhibitors at 1.3 events per 100 patient‐cycles. Third, the rate of VTE was comparable in trials of ND and R/R MM, in contrast to results from prior studies, mostly before routine thromboprophylaxis, which had shown a higher incidence in ND patients …”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Conversely, the risk is substantially higher with Rd in combination with proteasome inhibitors at 1.3 events per 100 patient‐cycles. Third, the rate of VTE was comparable in trials of ND and R/R MM, in contrast to results from prior studies, mostly before routine thromboprophylaxis, which had shown a higher incidence in ND patients …”
Section: Discussioncontrasting
confidence: 62%
“…First, while computing the event rate per 100 patient‐cycles, there is an implicit assumption that the risk of VTE remains stable over time. However, studies have shown that, in ND MM, majority of VTE events happen in the first 6 months of therapy . To address this, we have reported both the cumulative incidence and the event rate per 100 patient‐cycles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of thromboembolic events observed in myeloma treated with thalidomide/lenalidomide (thal/len) combined with dexamethasone or chemotherapy is identical to that observed in populations at high risk of venous thromboembolism, that is, orthopedic surgery, for which anticoagulant prophylaxis is systematically recommended. Although thromboprophylaxis is largely used in treated‐myeloma patients, the type and duration of treatment are debatable . A VTE primary prophylaxis strategy using low molecular weight heparin (LMWH) or aspirin according to a risk assessment model based on treatment received and level of risk was proposed by the International Myeloma Working Group …”
Section: Introductionmentioning
confidence: 99%